2015
DOI: 10.1155/2015/742792
|View full text |Cite
|
Sign up to set email alerts
|

Current Approach in the Diagnosis and Management of Uveitic Glaucoma

Abstract: Uveitic glaucoma (UG) typically is associated with very high intraocular pressure (IOP) and more intense optic nerve damage than other glaucoma types. This secondary glaucoma requires an early diagnosis and adequate management of both uveitis and glaucoma. It is mandatory to identify the mechanisms of IOP elevation that in many eyes have multiple combined mechanisms. Management of these patients commonly requires an interdisciplinary approach that includes a glaucoma specialist and rheumatologist to control th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 67 publications
(122 reference statements)
0
75
0
10
Order By: Relevance
“…Given suture removal led to IOP reduction within 24 hours, it implies that ocular hypertension is not associated with chronic pathologic responses, such as inflammation of the anterior chamber outflow pathways. [36][37][38] In addition, the data in the rat suture model indicated that the anterior chamber angle is not affected by the suture compression. 8 Furthermore, it is unlikely that we would have affected aqueous formation as it is associated with active transport mechanisms from the blood supply to the anterior eye structures.…”
Section: Discussionmentioning
confidence: 99%
“…Given suture removal led to IOP reduction within 24 hours, it implies that ocular hypertension is not associated with chronic pathologic responses, such as inflammation of the anterior chamber outflow pathways. [36][37][38] In addition, the data in the rat suture model indicated that the anterior chamber angle is not affected by the suture compression. 8 Furthermore, it is unlikely that we would have affected aqueous formation as it is associated with active transport mechanisms from the blood supply to the anterior eye structures.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding in a more racially diverse population also supports these latter two studies. Because of the potential adverse effect of inflammation on surgical outcomes, it is recognized best practice to ensure uveitic activity is well controlled before performing glaucoma surgery . However, often, this is not possible as acute uveitic activity can tip the balance of an already compromised outflow, leading to uncontrolled elevation of IOP not amendable to medical treatment alone.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the potential adverse effect of inflammation on surgical outcomes, it is recognized best practice to ensure uveitic activity is well controlled before performing glaucoma surgery. 16,17 However, often, this is not possible as acute uveitic activity can tip the balance of an already compromised outflow, leading to uncontrolled elevation of IOP not amendable to medical treatment alone. This was evident in more than one-third of trabeculectomy cases in this study having active uveitis at the time of surgery and had a significantly higher IOP than the GDI group, indicating surgery was performed in a more urgent setting.…”
Section: Discussionmentioning
confidence: 99%
“…In these conditions, in addition to elevated IOP from the underlying condition, there is also a very strong component of steroid response. 2 The rates of glaucoma in eyes with inflammation can range from 10%-20%. 3 The elevation of IOP can result from several factors, often in combination.…”
Section: Introductionmentioning
confidence: 99%